2009
DOI: 10.1021/jp910953w
|View full text |Cite
|
Sign up to set email alerts
|

Ion Specificity at the Peptide Bond: Molecular Dynamics Simulations of N-Methylacetamide in Aqueous Salt Solutions

Abstract: Affinities of alkali cations and halide anions for the peptide group were quantified using molecular dynamics simulations of aqueous solutions of N-methylacetamide using both nonpolarizable and polarizable force fields. Potassium and, more strongly, sodium exhibit an affinity for the carbonyl oxygen of the amide group, while none of the halide anions shows any appreciable attraction for the amide hydrogen. Heavier halides, however, interact with the hydrophobic methyl groups of N-methylacetamide. Using the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
148
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(166 citation statements)
references
References 49 publications
15
148
0
3
Order By: Relevance
“…form intermolecular hydrogen bond, which decreases with salt concentration. Our calculated radial distribution functions are very good in agreement with Heyda et al [69], who simulated salt solution of aqueous NMA system with different polarisable and non-polarisable force fields.…”
Section: Translational Diffusion and Structure Of The Solvation Shellsupporting
confidence: 89%
See 1 more Smart Citation
“…form intermolecular hydrogen bond, which decreases with salt concentration. Our calculated radial distribution functions are very good in agreement with Heyda et al [69], who simulated salt solution of aqueous NMA system with different polarisable and non-polarisable force fields.…”
Section: Translational Diffusion and Structure Of The Solvation Shellsupporting
confidence: 89%
“…Despite these latest advances, much less progress has been made in understanding the detailed interactions of cations and anions with polar and non-polar moieties of proteins. Recently, Jungwirth and co-workers [69] investigated the structure of the solvation shell of ions in aqueous NMA solution in presence of 1 M solutions of NaCl, KCl, KBr and NaBr using both polarisable and non-polarisable force fields. It was found that irrespective of the charge and size; the ionic solutes prefer water than NMA and also observed that in comparison to K + , Na + has a stronger affinity towards carbonyl oxygen of the amide group whereas none of the halide anions show any appreciable attraction for amide hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Note the two leftmost oxygen atoms on triglycine are degenerate, as are all the oxygens of the sulfite anion and every alanine monomer. tions (30). This spectrum is generally very similar to that of triglycine without sodium bromide, in that no new features are present.…”
mentioning
confidence: 57%
“…This behavior of cations and anions is well documented in simulations of model peptides in salt solutions. 29,32 Anions in both NaCl and NaI solutions interact more strongly with H R (Figure 2b). This preference might be related to the significant difference of solvent accessible areas of the two amide groups (11.1 Å 2 for N R vs 6.3 Å 2 for N L ).…”
Section: Alanine Dipeptide Simulationsmentioning
confidence: 96%